MICAgen Mice Recapitulate the Highly Restricted but Activation-Inducible Expression of the Paradigmatic Human NKG2D Ligand MICA - Kim, Younghoon; Born, Christina; Bléry, Mathieu; Steinle, Alexander (Frontiers in Immunology, 2020)
NKG2D is a potent activating immunoreceptor expressed on nearly all cytotoxic lymphocytes promoting their cytotoxicity against self-cells expressing NKG2D ligands (NKG2DL). NKG2DL are MHC class I-like glycoproteins which usually are not expressed on “healthy” cells. Rather their surface expression is induced by various forms of cellular stress, viral infection or malignant transformation. Hence, cell surface NKG2DL mark “dangerous” cells for elimination by cytotoxic lymphocytes and therefore can be considered as “kill-me” signals. In addition, NKG2DL are up-regulated on activated leukocytes which facilitates containment of immune responses. While the NKG2D receptor is conserved among mammals, NKG2DL genes have rapidly diversified during mammalian speciation, likely due to strong selective pressures exerted by species-specific pathogens. Consequently, NKG2DL genes are not conserved in man and mice, although their NKG2D-binding domains maintained structural homology. Human NKG2DL comprise two members of the MIC (MICA/MICB) and six members of the ULBP family of glycoproteins (ULBP1-6) with MICA representing the best-studied human NKG2DL by far. Many of these studies implicate a role of MICA in various malignant, infectious or autoimmune diseases. However, conclusions from these studies often were limited in default of supporting in vivo experiments. Here, we report a MICA-transgenic (MICAgen) mouse model that replicates central features of human MICA expression and function, and therefore constitutes a novel tool to critically assess and extend conclusions from previous in vitro studies on MICA. Similarly to humans, MICA transcripts are broadly present in organs of MICAgen mice, while MICA glycoproteins are barely detectable. Upon activation, hematopoietic cells upregulate and proteolytically shed surface MICA. Shed soluble MICA (sMICA) is also present in sera of MICAgen mice, but neither affects surface NKG2D expression of circulating NK cells nor their functional recognition of MICA-expressing tumor cells. Accordingly, MICAgen mice also show a delayed growth of MICA-expressing B16F10 tumors, not accompanied by an emergence of MICA-specific antibodies. Such immunotolerance for the xenoantigen MICA ideally suits MICAgen mice for anti-MICA-based immunotherapies. Altogether, MICAgen mice represent a valuable model to study regulation, function, disease relevance, and therapeutic targeting of MICA in vivo.